The Effects of Flipped Classroom Model with Heutagogy and Self-Efficacy Approach to Higher-Order Thinking Skills - Yowelna Tarumasely (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2022)
This study aimed to determine the effects of the application of heutagogy-based flipped classroom and self-efficacy on Higher-Order Thinking Skills (HOTS) for PAK Semester V students in the lesson planning course. The research method used was a quasi-experimental design with a two-by-two factorial design. The sample consisted of 48 students, consisting of the experimental and control groups. The research instrument was a questionnaire to measure self-efficacy and a test to measure higher thinking skills. Data analysis used two-way ANOVA, and all parametric assumption tests were performed at a significance value of 5%. The results of the study showed 1) there were differences in HOTS learning outcomes between groups of students with the heutagogy approach and students with andragogy approaches, 2) there were differences in HOTS learning outcomes between groups of students based on the level of self-efficacy, and 3) there was no interaction between Flipped Classroom with the heutagogy approach and self-efficacy on HOTS learning outcomes.